A “Good” Smoke? The Off-Label Use of Cannabidiol to Reduce Cannabis Use - Fortin, Davide; Di Beo, Vincent; Massin, Sophie; Bisiou, Yann; Carrieri, Patrizia; Barré, Tangui (Frontiers in Psychiatry, 2022)
Background Although cannabis use is common in France, it is still criminalized. Cannabidiol (CBD) products, including CBD-rich cannabis, are legally available. Although previous results suggested that CBD may have benefits for people with cannabis use disorder, there is a lack of data on cannabis users who use CBD to reduce their cannabis consumption. We aimed to identify i) correlates of this motive, and ii) factors associated with successful attempts to reduce cannabis use. Methods A cross-sectional online survey among French-speaking CBD and cannabis users was conducted. Logistic regressions were performed to identify correlates of using CBD to reduce cannabis consumption and correlates of reporting a large reduction. Results Eleven percent (n=105) of our study sample reported they primarily used CBD to reduce cannabis consumption. Associated factors included smoking tobacco cigarettes (adjusted odds ratio (aOR) [95% confidence interval (CI)] 2.17 [1.3-3.62], p=0.003) and drinking alcohol (aOR [95%CI] 1.8 [1.02-3.18], p=0.042). Of these 105, 83% used CBD-rich cannabis to smoke, and 58.7% reported a large reduction in cannabis consumption. This large reduction was associated with non-daily cannabis use (aOR [95% CI] 7.14 [2.4-20.0], p<0.001) and daily CBD use (aOR [95%CI] 5.87 [2.09-16.47], p=0.001). A reduction in cannabis withdrawal symptoms thanks to CBD use was the most-cited effect at play in self-observed cannabis reduction. Conclusions Cannabis use reduction is a reported motive for CBD use - especially CBD-rich cannabis to smoke - in France. More studies are needed to explore practices associated with this motive and to accurately assess its CBD effectiveness.